2003
DOI: 10.1177/0115426503018005427
|View full text |Cite
|
Sign up to set email alerts
|

Tube Feeding in Mechanically Ventilated Critically Ill Patients: A Prospective Clinical Audit

Abstract: This audit in extremely severe intensive care patients identified several factors that impair gastrointestinal function and preclude EN at any stage, namely early EN. Nutrition management must take into account concurrent therapies, given their potential interference with nutrition and organ function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…22,29,44 The use of prokinetic medications such as erythromycin and metoclopramide is effective in this population at decreasing GRVs and increasing tolerance of gastric enteral nutrition. [45][46][47] Metoclopramide is the most commonly used agent and acts by increasing antral and small intestinal motility.…”
Section: Use Of Prokinetic Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,29,44 The use of prokinetic medications such as erythromycin and metoclopramide is effective in this population at decreasing GRVs and increasing tolerance of gastric enteral nutrition. [45][46][47] Metoclopramide is the most commonly used agent and acts by increasing antral and small intestinal motility.…”
Section: Use Of Prokinetic Medicationsmentioning
confidence: 99%
“…22,54 A meta-analysis of randomized controlled trials in which outcomes in critically ill patients receiving gastric feedings versus critically ill patients receiving duodenal feedings showed no difference in mortality, risk of diarrhea, length of ICU stay, or risk of aspiration or pneumonia. 55 Conflicting evidence is provided by smaller studies 29,44 with less rigorous design, where intolerance in critically ill patients receiving gastric feedings is reported. Evidence-based practice guidelines developed by A.S.P.E.N.…”
Section: Consideration Of Postpyloric Feeding Accessmentioning
confidence: 99%
“…Ravasco and Camilo also only considered EN appropriate once hemodynamic stability was achieved. 18 Other studies have noted delays in EN initiation or interruptions in EN due to factors associated with hemodynamic instability. 20,22 Based on this information, it is conceivable that the delays due to hemodynamic instability seen in our study were unavoidable and justifiable.…”
Section: Early En Recommendationsmentioning
confidence: 97%
“…In the literature, the proportion of ICU patients beginning EN within 48 hours of admission ranged from 22% to 50%. 18,19 Heyland et al 20 found that of those ICU patients started on EN, the average initiation time was 3.1 days after ICU admission, and Rice et al 21 found that EN was started between days 2 and 4 of mechanical ventilation, presumably initiated after the patient was admitted to the ICU. The results of our study showed a 16%-44% greater adherence to the early EN guideline compared with those results in the literature.…”
Section: Early En Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation